Globalization and the South some critical issues - Khor, Martin (Third World Network, 2000)
This book examines the implications of some of the main features of the globalization process for developing countries. It also makes several proposals for developing countries in considering national-level policies to face the globalization challenge, as well as for coordination among developing countries in facing negotiations or making proposals at the international level.